Seroprevalence of Bluetongue virus in goats (Capra hircus) of the Northern Region of Peru - Escano L., Josselyn (2022)
Bluetongue is an endemic disease in tropical and subtropical regions and the virus that causes the disease is transmitted by mosquito vectors of the genus Culicoides. The aim of this study was to determine the seroprevalence of the Bluetongue virus (BTV) in goats from the departments of Tumbes, Piura, Lambayeque, Cajamarca and La Libertad (Peru). Blood samples (n=424) were collected from goats older than 6 months of age, without clinical signs of disease and reared in extensive production systems between June and October 2017. The sera were analysed with commercial ELISA competition kits to determine antibodies against BTV. A seroprevalence of 23.8% (95% CI 19.84-28.16) was found. The results by department indicate that 34.9% (81/232), 20.9% (13/62), 9.5% (4/42) and 6.0% (3/50) and 0% (0/38) of samples from Piura, Tumbes, Cajamarca. Lambayeque and La Libertad, respectively, had antibodies against BTV. The seropositivity showed a positive association (p<0.05) with the age of the goats and negative (p<0.05) with the altitude of rearing.